Structural Improvement Planning of Road Pavement with Modified Porous Asphalt Mixture using AASHTO 1993 - Arief Aszharri; Dimas Ariezky Susetyo; Nadra Mutiara Sari (CIVED, 2025)
The new technology that is being developed is porous asphalt pavement structures, which are made for road segments with less dense traffic. This structure is designed to include facilities such as parking lots, bicycle lanes, pedestrian sidewalks, and tennis court areas. This study involves the analysis of calculation results based on secondary field data and experimental data from laboratory-scale experiments. The design of the road pavement is based on the AASHTO 1993 method. The field data used includes information on the LHR (Load History Record) of the Dawuan Highway (Cikampek) section, the CBR (California Bearing Ratio) value of the subgrade, and the existing pavement conditions (including existing pavement structures and deflection data). Meanwhile, experimental data comes from testing the resilient modulus of porous asphalt mixtures using Cariphalte asphalt and additional gilsonite material with optimal levels. The resilient modulus value was obtained from laboratory testing using the Universal Material Testing Apparatus (UMATTA). The results of this study produced a pavement design using a gilsonite mixture that produced a thinner thickness than standard AC-WC materials. For example, for segment 3 with a modified mixture, the pavement thickness is 13 cm, while the standard AC-WC produces a thickness of 20 cm. It can be seen that using a modified Gilsonite mixture requires an overlay layer 7 cm thinner than using a standard AC-WC mixture.